2017
DOI: 10.1063/1.4975688
|View full text |Cite
|
Sign up to set email alerts
|

Is Br2 hydration hydrophobic?

Abstract: The spectroscopic properties of bromine in aqueous systems suggest it can behave as either hydrophilic or hydrophobic solute. In small water clusters, the halogen bond and the hydrogen-halogen interaction are responsible for its specific way of binding. In water hydrates, it is efficiently hosted by two different cages forming the crystal structure and it has been frequently assumed that there is little or no interaction between the guest and the host. Bromine in liquid solution poses a challenging question du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The initial interpretation of the observed electronic shifts in ultraviolet and visible spectra of bromine clathrate assumed that halogen bonding could not be responsible since all the water lone‐pairs are involved in hydrogen bonding of the water lattice and thus not available for halogen bonding . In contrast the much larger blue‐shifts observed in bromine aqueous solutions were consistent with the formation of halogen bonding interactions . However evidence of halogen bonding in clathrate cages was strongly suggested in ab initio local correlation calculations through an energy partitioning analysis and calculation of the electronic shifts at selected geometries .…”
Section: Introductionmentioning
confidence: 99%
“…The initial interpretation of the observed electronic shifts in ultraviolet and visible spectra of bromine clathrate assumed that halogen bonding could not be responsible since all the water lone‐pairs are involved in hydrogen bonding of the water lattice and thus not available for halogen bonding . In contrast the much larger blue‐shifts observed in bromine aqueous solutions were consistent with the formation of halogen bonding interactions . However evidence of halogen bonding in clathrate cages was strongly suggested in ab initio local correlation calculations through an energy partitioning analysis and calculation of the electronic shifts at selected geometries .…”
Section: Introductionmentioning
confidence: 99%
“…An increment in inhibitory activity was noticed in O10 , by substituting the phenyl ring at para position with methoxy (IC 50 =95.7±0.51 μM). Further increase in activity was observed in O4 where substitution is done by bromo, at para position (IC 50 =92.3±0.14 μM) as reported that bromo substituted compounds may possess better inhibitory activity as compared to others [42] which may happen due to hydrophobic nature of bromine and bromine being more polarizable than hydrogen which could influence the electron density distribution within the molecule, affecting its interactions with the active site residues of the enzyme [43] . Similar behavior was observed when in O3 , the moiety was substituted at para position by chloro group, (IC 50 =88.8±0.14 μM) as shown in Figure 3.…”
Section: Resultsmentioning
confidence: 89%
“…Halogen molecules like Br 2 or Cl 2 are excellent probes of their surrounding environment. The beautiful spectroscopic experiments by Janda and Apkarian’s groups showed that the maximum absorption peak in UV–vis absorption experiments shifts in different amounts in aqueous systems. The observed blue-shift is due to the intermolecular interactions present, from the “classical” halogen bond (XB) to some variants. The latest diffraction experiments by Udachin et al confirmed that Cl 2 is hosted in a cage almost too small to fit in, and so it also is for Br 2 . , This result evidenced that the guest–host interactions should go beyond the weak van der Waals regime since the free diameter of the 5 12 cages is estimated at ∼5.0 Å, and the van der Waals size of dichlorine is 5.5 Å. Recently, our group showed that the stabilization of Cl 2 @5 12 , Cl 2 @5 12 6 2 , and Br 2 @5 12 6 2 is the result of a subtle balance of forces.…”
Section: Introductionmentioning
confidence: 99%